Le patrimoine paysager comme élément constitutif d’un espace de nature protégé touristique - Caroline Pouliquen (Projets de Paysage)
The landscape in protected areas is often linked to the notion of “natural heritage.” Protected areas generally have two missions, environmental protection and tourism, with the latter often considered as something bad for the landscape. Even if protected areas seem to accept this activity in their official laws and missions, they often have an ambiguous relationship with tourism. Their relationship with “natural landscape” is also very ambiguous, as the people deciding what is natural or not are the experts of these protected areas. Among the three European protected areas that we studied, the only protected area that seems to really accept tourism is the Lake District National Park (UK). In this place, tourism is understood as an element of heritage. “Natural heritage” no longer seems “natural” and is becoming a “landscape heritage” in which every human activity is accepted.